Guatemala : Elements of a Transport and Logistics Strategy - Dumitrescu, Anca C. (World Bank, Washington, DC, 2015)
This document has been produced by the World Bank to support the Government of Guatemala as it improves its transport and logistics sector management in pursuit of enhanced country competitiveness. It identifies and defines elements of a National Transport and Logistics Strategy (NTLS) through the development of a methodology which analyzes bottlenecks and related costs along the main logistics corridors. It does so with a view to (a) mobilizing support in the trading community (essentially private sector) for logistic service improvements, (b) identifying the need for broader public-sector reforms in transport which indirectly impact logistics performance, and (c) helping the Government to set sector priorities and hence to prioritize public investment. At the same time, it points out where improved data and monitoring of performance are needed in order to better quantify economic costs, diagnose key logistics issues, and track improved performance. It thereby proposes, as part of the set of recommended activities, to build the Government of Guatemala s capacity to measure performance and take action. While the document is based on sound analysis of some aspects of the country s logistics system, it must be considered primarily a starting point which is subject to broad country dissemination and debate by public and private stakeholders.